Stopa procentowa a wartość rynkowa aktywów i zobowiązań firmy ubezpieczeniowej w relacji do czasu trwania nadwyżki w aspekcie struktury kapitałowej - Szkutnik, Włodzimierz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents a discussion concerning differences in the methods of measuring financial surplus of insurance companies. It is important to determine the relationships among interest rate, capital structure and market value during the period surplus. These relationships may lead to a conclusion that at a high level of risk, higher interest rate risk is connected with higher market values. On the other hand, it is possible to get results coming from q-Tobin model that oppose this thesis. However, the condition of making idealized, though partly justified, assumptions must be fulfilled. The article does not give definitive answer to this dispute. It only presents some comments concerning these concepts. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 434-440